Getting a handle on lipid droplets: Insights into ER–lipid droplet tethering - Nguyen, Truc B. (J Cell Biol, 2019)
Lipid droplets (LDs) are hubs for lipid metabolism that form membrane contact sites with multiple organelles. In this issue, Hariri et al. (2019. J. Cell Biol. https://doi.org/10.1083/jcb.201808119) reveal the functions of Mdm1-mediated endoplasmic reticulum (ER)–LD tethering in yeast and Datta et al. (2019. J. Cell Biol. https://doi.org/10.1083/jcb.201808133) identify a role for the Mdm1 orthologue, Snx14, as an ER–LD tether that regulates lipid metabolism in human cells.